2006
DOI: 10.1002/hyp.6237
|View full text |Cite
|
Sign up to set email alerts
|

Temperature in lowland Danish streams: contemporary patterns, empirical models and future scenarios

Abstract: Abstract:Continuous temperature measurements at 11 stream sites in small lowland streams of North Zealand, Denmark over a year showed much higher summer temperatures and lower winter temperatures along the course of the stream with artificial lakes than in the stream without lakes. The influence of lakes was even more prominent in the comparisons of colder lake inlets and warmer outlets and led to the decline of cold-water and oxygen-demanding brown trout. Seasonal and daily temperature variations were, as ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 35 publications
(56 reference statements)
3
40
0
2
Order By: Relevance
“…The amount of macrophytes in the river is known to have an effect on suspended sediment transport, creating temporary storage that traps sediment and prevents scour along most of the river channel perimeter (Svendsen and Kronvang, 1993). A warmer climate will prolong the growing season of macrophytes because the temperature of the water increases (Webb et al, 2003;Pedersen and Sand-Jensen, 2007), and the estimated reduction in river discharge during autumn will reduce the degradation of the macrophytes (Ovesen et al, 2000;Wade et al, 2002). This will make macrophytes store sediment for a longer period during autumn and early winter in the scenario period.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of macrophytes in the river is known to have an effect on suspended sediment transport, creating temporary storage that traps sediment and prevents scour along most of the river channel perimeter (Svendsen and Kronvang, 1993). A warmer climate will prolong the growing season of macrophytes because the temperature of the water increases (Webb et al, 2003;Pedersen and Sand-Jensen, 2007), and the estimated reduction in river discharge during autumn will reduce the degradation of the macrophytes (Ovesen et al, 2000;Wade et al, 2002). This will make macrophytes store sediment for a longer period during autumn and early winter in the scenario period.…”
Section: Discussionmentioning
confidence: 99%
“…Air-water temperature relationships were widely used for stream temperature prediction in the face of climate warming [32], as well as for the identifi cation of groundwater-fed sites, as linear models of such reaches have lower slopes and higher intercepts than their meteorological control counterparts [33]. In the present study, similar to groundwater effect, lower slopes and higher intercepts refl ected sewage infl ows (a = 0.58, b = 8.02) and the net result of tributary infl ow and releases from reservoir (a = 0.61, b = 5.50); however, according to previous studies, typical groundwater-fed streams have generally lower regression slopes [31,33].…”
Section: Air-water Temperature Relationshipsmentioning
confidence: 99%
“…While the logistic models have been shown to be a considerable improvement over the linear model for some rivers (Erickson and Stefan, 2000;Pedersen and Sand-Jensen, 2007), some studies have suggested ther is little advantage in using the more complex logistic models for their rivers (Webb et al, 2003;Neumann et al, 2003).…”
Section: Empirical Regression Models For Water Temperaturementioning
confidence: 99%
“…and anthropogenic disturbances of the natural thermal regime such as deforestation and hydroelectric development (Gras, 1969;Beschta et al, 1987;Benyahya et al, 2008). In recent years a number of studies have identified global warming as another major influence of water temperature (Sinokrot et al, 1995;Webb, 1996;Mohseni et al, 1998Pedersen and Sand-Jensen, 2007). Eaton and Scheller (1996) suggest that cold water fish densities in the United States could decline by as much as 50 percent if river temperatures rise due to an increase carbon dioxide levels in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%